PROCESS MODEL FOR THE THEORETICAL FRAMEWORK OF MANAGEMENT DECISIONS SUPPORT SYSTEMS - MELNYCHUK, Volodymyr; KHLYSTUN, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines how the correct use of management decision-making tools helps enterprises achieve their short- and long-term goals. This will allow managers to make balanced decisions that will primarily benefit the enterprise or organization. It will also allow a comprehensive approach to solving the problems that arise in their activities. It has been established that the management decision support system is a multifunctional tool that requires detailed analysis in high-quality journals. The history of the management decision support system was analyzed. It was found that the vast majority of domestic scientists research applied aspects of developments in the field of management decision support systems. And the first scientific works were based on experimental research. It is noted that the first experimental studies were based on creating a decision-making environment. The need to introduce a management decision support system into the activities of institutions and organizations has been revealed. A process model of the theoretical foundations of the management decision support system and strategies for improving the research of the management decision support system are proposed. Its main components are described, and the main implementation problems are identified. It has been established that any constructed model or process model of management decision support system theoretical foundations contains appropriate components that must be applied comprehensively. These components have their own characteristics and are used in different situations. For their application, it is necessary to implement actions of a different nature. First of all, it is obtaining timely, complete, and high-quality information through the interaction of the software complex with available management information. A management decision support system requires a significant number of experts in the chosen field of knowledge who can manage data and process it in large quantities. Accordingly, the more complete the information, the greater the chance of making the right management decision, which can affect the further activities of the enterprise or organization.